2018
DOI: 10.1002/hsr2.101
|View full text |Cite
|
Sign up to set email alerts
|

Getting the right fit: Convergence between preferred and perceived involvement in treatment decision making among medical oncology outpatients

Abstract: Background and AimsWhile cancer patients' preferences for their level of involvement in treatment decision making (TDM) vary, previous research indicates a large proportion of patients are not experiencing TDM that meets their preferences. Evidence is needed to identify the characteristics of cancer patients who are less likely to report experiencing their preferred level of involvement in TDM, so that appropriate decision‐making support can be provided to them. We examined in a sample of medical oncology outp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 37 publications
0
7
1
Order By: Relevance
“…Most studies ( N = 13) included breast cancer patients, 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 two studies included patients with haematologic cancer, 39 , 40 two studies lung cancer patients, 41 , 42 one study colorectal cancer patients, 43 two studies prostate cancer patients 44 , 45 and others included various cancers. 9 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 More studies were performed in Western countries, 9 , 27 , 28 , 29 , 30 , 31 , 33 , 35 , 36 , 39 , 40 , 42 , 44 , 45 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ,…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Most studies ( N = 13) included breast cancer patients, 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 two studies included patients with haematologic cancer, 39 , 40 two studies lung cancer patients, 41 , 42 one study colorectal cancer patients, 43 two studies prostate cancer patients 44 , 45 and others included various cancers. 9 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 More studies were performed in Western countries, 9 , 27 , 28 , 29 , 30 , 31 , 33 , 35 , 36 , 39 , 40 , 42 , 44 , 45 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ,…”
Section: Resultsmentioning
confidence: 99%
“… 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 36 , 37 , 42 , 44 Five studies included advanced stage cancer patients, 35 , 41 , 46 , 48 , 51 eight studies included all stages, 9 , 34 , 38 , 47 , 52 , 53 , 54 and for six studies cancer stage was not reported. 39 , 40 , 43 , 45 , 49 , 50 Most studies used a cross‐sectional design in which patients’ preferred and perceived decision role were measured after treatment decision. 9 , 26 , 27 , 29 , 30 , 32 , 33 , 35 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For now, as the 4Ps tool does not provide a common route whereby a higher degree of all types of participation is consequentially better, a match-rank between preferences and experiences is important in order to visualise what constitutes ‘good’ and ‘bad’ patient participation, respectively [ 26 , 27 ]. By using a match-rank, the fit of the participation experienced by the patient relative to the preference profile is measured, making it possible to illustrate quality of care from the perspective of both individual and group-level data [ 28 ].…”
Section: Discussionmentioning
confidence: 99%